Free No More - Ben R. Blankenship (Journal of Applied Communications, 1982)
We have for many years in the U.S. Department of Agriculture been running a huge vanity press, I believe, catering more to the whims of authors and their administrators and the political appointees rather than first considering markets for the publications themselves.